Fabrication and structural characterization of bismuth niobate thin films grown by chemical solution deposition - Goncalves, L. F. [UNESP]; Cortes, J. A. [UNESP]; Ranieri, M. G. A. [UNESP]; Destro, F. B. [UNESP]; Ramirez, M. A. [UNESP]; Simoes, A. Z. [UNESP] (Springer, 2015)
Bi3NbO7 (BNO) thin films were deposited on Pt/TiO2/SiO2/Si (100) substrates at room temperature from the polymeric precursor method. X-ray powder diffraction and transmission electron microscopy were used to investigate the formation characteristics and stability range of the tetragonal modification of a fluorite-type solid solution. The results showed that this tetragonal, commensurately modulated phase forms through the intermediate formation of the incommensurately modulated cubic fluorite phase followed by the incommensurate-commensurate transformation. The 200 nm thick BNO films exhibit crystalline structure, a dielectric constant of 170, capacitance density of 200 nF/cm(2), dielectric loss of 0.4 % at 1 MHz, and a leakage current density of approximately 1 x 10(-7) A/cm(2) at 5 V. They show breakdown strength of about 0.25 MV/cm. The leakage mechanism of BNO film in high field conduction is well explained by the Schottky and Poole-Frenkel emission models. The 200 nm thick BNO film is suitable for embedded decoupling capacitor applications directly on a printed circuit board.